2023
DOI: 10.3390/life13081779
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease as a Paradoxical Reaction to Anti-TNF-α Treatment—A Review

Ioana Ruxandra Mihai,
Alexandra Maria Burlui,
Ioana Irina Rezus
et al.

Abstract: TNF-α inhibitors (TNFis) have revolutionized the treatment of certain chronic immune-mediated diseases, being widely and successfully used in rheumatic inflammatory diseases, and have also proved their efficacy in the treatment of inflammatory bowel disease (IBD). However, among the side effects of these agents are the so-called paradoxical effects. They can be defined as the appearance or exacerbation of a pathological condition that usually responds to this class of drug while treating a patient for another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Inflammatory bowel diseases (IBDs) such as Crohn's disease (CD) and ulcerative colitis are the result of an over-reactive immune system that targets the gastrointestinal tissue, resulting in inflammation and subsequent abdominal pain, bleeding, weight loss, and malnutrition [53][54][55][56][57]. Several studies have shown that LFA-1 plays a crucial role in the development of the disease.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs) such as Crohn's disease (CD) and ulcerative colitis are the result of an over-reactive immune system that targets the gastrointestinal tissue, resulting in inflammation and subsequent abdominal pain, bleeding, weight loss, and malnutrition [53][54][55][56][57]. Several studies have shown that LFA-1 plays a crucial role in the development of the disease.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Moreover, IBD can manifest as a paradoxical reaction to TNFi treatment. 8 Anti-TNF agent therapy may potentially increase the risk of IBD. 9 Tofacitinib has been employed in the treatment of axSpA and IBD.…”
mentioning
confidence: 99%